El crecimiento del comercio en la región Loreto y su relación con la rentabilidad de la caja municipal de ahorro y crédito de Maynas S.A durante el periodo 2007 – 2021 - Ramirez Chufandama, Amalia; Vela Bardales, Diego Rafael (Universidad Nacional de la Amazonía Peruana, 2024)
This study analyzes the relationship between economic growth and the financial operations of the Maynas Municipal Savings and Credit Fund in the Loreto region, Peru, during the period 2007-2021. Using a quantitative and non-experimental approach, Spearman's correlation coefficient was used to examine three key hypotheses. The results revealed a moderate correlation between the growth of commerce in Loreto and the profitability of the Municipal Fund, with a Spearman coefficient of 0.450, indicating that, although there is a positive influence of commerce on profitability, there are other significant factors at play. Likewise, a weak but statistically significant correlation (rho of 0.229) was identified between the growth of commerce and direct credits granted by the Municipal Fund. On the other hand, a strong relationship (rho of 0.736) was found between the gross value added of the region and direct deposits in the Municipal Fund. These findings suggest that Loreto's economic dynamics play a crucial role in the financial health of the Municipal Fund, but also highlight the need to consider a diversity of factors in making financial and credit decisions.

Este estudio analiza la relación entre el crecimiento económico y la operativa financiera de la Caja Municipal de Ahorro y Crédito de Maynas en la región de Loreto, Perú, durante el periodo 2007-2021. Mediante un enfoque cuantitativo y no experimental, se empleó el coeficiente de correlación de Spearman para examinar tres hipótesis clave. Los resultados revelaron una correlación moderada entre el crecimiento del comercio en Loreto y la rentabilidad de la Caja Municipal, con un coeficiente de Spearman de 0.450, indicando que, aunque hay una influencia positiva del comercio en la rentabilidad, existen otros factores significativos en juego. Asimismo, se identificó una correlación débil pero estadísticamente significativa (rho de 0.229) entre el crecimiento del comercio y los créditos directos otorgados por la Caja Municipal. Por otro lado, se encontró una fuerte relación (rho de 0.736) entre el valor agregado bruto de la región y los depósitos directos en la Caja Municipal. Estos hallazgos sugieren que la dinámica económica de Loreto juega un papel crucial en la salud financiera de la Caja Municipal, pero también resalta la necesidad de considerar una diversidad de factores en la toma de decisiones financieras y de crédito.
Keywords: Comercio; Economía regional; Crecimiento económico; Cajas de ahorro; Rentabilidad; https://purl.org/pe-repo/ocde/ford#5.02.01